Developing Uniform Performance Measures for Policing in the United States: A Pilot Project in Four Agencies, 2008-2009 - Davis, Robert C. ([Verlag nicht ermittelbar], 2013)
Between 2008 and 2009, the research team gathered survey data from 458 members of the community (Part 1), 312 police officers (Part 2), and 804 individuals who had voluntary contact (Part 3), and 761 individuals who had involuntary contact (Part 4) with police departments in Dallas, Texas, Knoxville, Tennessee, and Kettering, Ohio, and the Broward County, Florida Sheriff's Office. The surveys were designed to look at nine dimensions of police performance: delivering quality services; fear, safety, and order; ethics and values; legitimacy and customer satisfaction; organizational competence and commitment to high standards; reducing crime and victimization; resource use; responding to offenders; and use of authority. The community surveys included questions about police effectiveness, police professionalism, neighborhood problems, and victimization. The officer surveys had three parts: job satisfaction items, procedural knowledge items, and questions about the culture of integrity. The voluntary police contact and involuntary police contact surveys included questions on satisfaction with the way the police officer or deputy sheriff handled the encounter.